PEMANFAATAN MINYAK BIJI RAMI (LINSEED OIL) DAN GLISEROL BY-PRODUCT BIODIESEL UNTUK PEMBUATAN VERNIS ALAMI - Sutanti, Sri; Purnavita, Sari; Sriyana, Herman Yoseph (Universitas Diponegoro, 2013)
Abstract Varnish is coating material that is produced by using polymer. ActuallyÂ natural varnish is produced by manufacturing natural polymer like gondorukem. The research is to study about optimizing ofÂ reactant composition as the ratio of OH/COOH and operation temperature in the process of making natural varnish from gondorukem, linseed oil and glycerol by-product biodiesel using the alcoholysis method. The reaction is done in the reactor using agitator. The reaction consists of two steps, 1). the forming of monoglyceride, 2). the forming of varnish. Both steps of reaction is done at the same temperature (200oC, 220oC, 240oC and 260oC). Reactant ratio is used as equivalent ratio OH/COOH: 1,1; 1,2; and 1,3. We analyze free glycerol concentration in the first step reaction andÂ acid value in the second step reaction. The best result is obtained in ratio 1,2 and operation temperature 260oC. Key word: natural varnish, alcoholysis, equivalent ratio OH/COOH, linseed oil, glycerol by-product biodiesel.